2018
DOI: 10.2298/fil1816633d
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Keller-Segel model with Atangana-Baleanu fractional derivative

Abstract: The new definition of the fractional derivative was defined by Atangana and Baleanu in 2016. They used the generalized Mittag-Leffler function with the non-singular and non-local kernel. Further, their version provides all properties of fractional derivatives. Our aim is to analyse the Keller-Segel model with Caputo and Atangana-Baleanu fractional derivative in Caputo sense. Using fixed point theory, we first show the existence of coupled solutions. We then examine the uniqueness of these solutions. Finally, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Until now, to the best of our knowledge, the works on analysis existence and regularity for ODEs and PDEs with Atangana-Baleanu derivative is very limited. In [18], the authors show the existence of the Keller-Segel model with Caputo and Atangana-Baleanu fractional derivative using fixed point theory. In [24], the fractional logistic model concerned with Atangana-Baleanu fractional derivative is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, to the best of our knowledge, the works on analysis existence and regularity for ODEs and PDEs with Atangana-Baleanu derivative is very limited. In [18], the authors show the existence of the Keller-Segel model with Caputo and Atangana-Baleanu fractional derivative using fixed point theory. In [24], the fractional logistic model concerned with Atangana-Baleanu fractional derivative is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Fractional calculus has been appealing to many researchers over the last decades [1][2][3][4][5]. Some researchers have found that different fractional derivatives with different singular or nonsingular kernels need to be identified by real-world problems in different fields of engineering and science [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Fractional integral operators are very useful in mathematical inequalities. e authors have established fractional integral inequalities due to different fractional integral operators, see [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Many authors have used Mittag-Leffler function to define fractional integral operators.…”
Section: Introductionmentioning
confidence: 99%